Models of care in forensic psychiatry - Kennedy, Harry (Seminars in forensic psychiatry, 2024)
A model of care defines how health services are delivered. It typically has four elements: goals; pathways and processes; treatment programmes; and evaluation in which a logic model relates resources delivered to sustained health gains and defined outcome measures. The elements of therapeutic security – environmental, relational, procedural and managerial – influence specifically forensic models of care. Services that manage serious risks must ensure judgement support frameworks, resilience and sustainable levels of service. Population needs and prison morbidity surveys should shape services at a national level. Prison in-reach services based on screening, diversion and continuity of care are an integral part of a forensic model of care, along with highly supportive and structured community services for the conditionally discharged patient. Forensic psychiatry services may to some extent be a bellwether for both positive and problematic aspects of the larger model of care for mental health for a population and may be the first places to see signs of service strain elsewhere. Tertiary highly specialised services should aim for excellence. Excellence is the process of leading continuous improvement of outcomes for patients through the virtuous cycle of research, development, teaching and training. Investing in excellence as a key priority and value is essential.